Ð¡Ñ‚Ñ€Ð°Ñ‚ÐµÐ³Ð¸Ð¸ Ñ…Ð¾Ð»Ð¾Ð´Ð¾ÑƒÑÑ‚Ð¾Ð¹Ñ‡Ð¸Ð²Ð¾ÑÑ‚Ð¸ Ð±ÐµÑÐ¿Ð¾Ð·Ð²Ð¾Ð½Ð¾Ñ‡Ð½Ñ‹Ñ… - Gulevsky, A. K.; Relina, L. I. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2024)
The review is devoted to the classification of invertebrates’ cold-hardiness types. Classically distinguished strategies of cold-hardiness and their biochemical mechanisms are considered in the research, as well as the data of research results requiring new approaches to invertebrates’ cold-hardiness classification are discussed.